# Thread: solving for y

1. ## solving for y

solve:

(11/4 y^1/4) - (3/2y^-3/4) = 0

2. Originally Posted by samtheman17
solve:

(11/4 y^1/4) - (3/2y^-3/4) = 0
if you mean ...

$\displaystyle \frac{11}{4} y^{\frac{1}{4}} - \frac{3}{2} y^{-\frac{3}{4}} = 0$

then start by multiplying every term by $\displaystyle y^{\frac{3}{4}}$

3. okay..........

so far i have

(22/4 y ^3/16) - (6/2y ^ -9/16)

now i make the others have the same denominator so.....

(22/4 y ^ 3/16) - (12/4y ^ -9/16) ......

now im not sure how to subtract exponents

4. Originally Posted by samtheman17
okay..........

so far i have

(22/4 y ^3/16) - (6/2y ^ -9/16)

now i make the others have the same denominator so.....

(22/4 y ^ 3/16) - (12/4y ^ -9/16) ......

now im not sure how to subtract exponents
you do not multiply the exponents.

note the following ...

$\displaystyle y^{\frac{3}{4}} \cdot y^{\frac{1}{4}} = y^{\frac{3}{4} + \frac{1}{4}} = y$

$\displaystyle y^{\frac{3}{4}} \cdot y^{-\frac{3}{4}} = y^{\frac{3}{4} - \frac{3}{4}} = y^0 = 1$

5. ohh okay, so

(11/4 y) - (3/2) = 0

then solve for y and get 6/11

thanks you !